In Vitro Multi-Bioactive Potential of Enzymatic Hydrolysis of a Non-Toxic Jatropha curcas Cake Protein Isolate - Javier, Olloqui Enrique; Alejandro, González-Rodríguez Maurilio; Elizabeth, Contreras-López; Guadalupe, Pérez-Flores Jesús; Emmanuel, Pérez-Escalante; Carlos, Moreno-Seceña Juan; Daniel, Martínez-Carrera (Molecules (Basel, Switzerland), 2024)
The Jatropha curcas cake, a protein-rich by-product of biofuel production, was the subject of our study. We identified and quantified the ACE inhibitory, antioxidant, and antidiabetic activities of bioactive peptides from a Jatropha curcas L. var Sevangel protein isolate. The protein isolate (20.44% recovered dry matter, 38.75% protein content, and 34.98% protein yield) was subjected to two enzyme systems for hydrolysis: alcalase (PEJA) and flavourzyme (PEJF), recording every 2 h until 8 h had passed. The highest proteolytic capacity in PEJA was reached at 2 h (4041.38 ± 50.89), while in PEJF, it was reached at 6 h (3435.16 ± 59.31). Gel electrophoresis of the PEJA and PEJF samples showed bands corresponding to peptides smaller than 10 kDa in both systems studied. The highest values for the antioxidant capacity (DPPH) were obtained at 4 h for PEJA (56.17 ± 1.14), while they were obtained at 6 h for PEJF (26.64 ± 0.52). The highest values for the antihypertensive capacity were recorded at 6 h (86.46 ± 1.85) in PEJF. The highest antidiabetic capacity obtained for PEJA and PEJF was observed at 6 h, 68.86 ± 8.27 and 52.75 ± 2.23, respectively. This is the first report of their antidiabetic activity. Notably, alcalase hydrolysate outperformed flavourzyme hydrolysate and the cereals reported in other studies, confirming its better multi-bioactivity.